Correlation between riparian vegetation characteristics and water quality in selected forest stands, Malaysia - Murad, Azliza (2012)
Riparian zones have been accounted as the most productive ecosystems and also one of the most sensitive to human influences and potentially most threatened ecosystems. Within production forest of Permanent Forest Reserve in Peninsular Malaysia buffer zone is usually demarcated in the regulation, but the size of the buffer zones varies depending on the state’s law and also the steepness and width of the stream. Despite that, logging activities still contributed significantly to the degradation of riparian zones due to the poor planning of logging roads and skidder trails. The study was conducted in Pasoh Forest Reserve (PFR) and Ayer Hitam Forest Reserve (AHFR). The main objectives of this study are to; 1) characterize the riparian plant communities in lowland forest based on species composition, structure and diversity; 2)assess the effect of logging activities and other disturbance on water quality and riparian plant communities in lowland forest; and 3) correlate the composition, structure and diversity of riparian vegetation with the water quality parameters. Three different types of forest were chosen for each site. For PFR; Compt. 47 has been logged on October 2009; Compartment 55 was logged on 2005 and finally, undisturbed forest of Compartment 51. While in AHFR, Compartment 15 and Compartment 13 were logged over forest since 1950’s and Compartment 14 was a logged over forest since 1960’s. Water quality parameters were measured in each station by In-situ for Dissolved Oxygen (DO) and pH and Ex-situ for Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia Nitrogen (NH3N) and Total Suspended Solids (TSS) to establish the current water quality status in particular river at both study sites. Canonical Correspondence Analysis (CCA) method was used to elucidate the relationship between riparian plant communities with their adaptation to the stream water quality and summarize the variation in the relative frequencies of the response variables (species) (Leps and Smilauer, 2003). Additionally, Cluster Analysis by using ray-Curtis Similarity Coefficient was performed to establish a dendrogram inferring similarity of species composition between those compartments. For water quality analysis, One Way of Variance (ANOVA) and t-test were used to compare water quality status among stations within study areas. Results showed that a total of 1362 individual tree enumerated belonging to 308 species,188 genera and 75 families were recorded in PFR. In AHFR however, the numbers were lesser than PFR with 1217 individuals from 108 species, 89 genera and 51 families. Composition of species showed that Pometia pinnata (Kasai) is the most abundant species for trees while shrubs of Clidemia hirta (Senduduk bulu) is the most abundant shrubs in PFR. In AHFR, Saraca declinata Gapis) is the most abundant tree while Donax grandis Bemban) is the most abundant for non tree species. For Importance Value Index (IVI), the IVI based on family in PFR is contributed largely from Sapindaceae with the value of 1.025 followed by Annonaceae (0.9682), Dipterocarpaceae (0.7217), Leguminosae (0.5945) and Euphorbiaceae (0.5681). In AHFR, the highest IVI based on family is recorded mostly by family Dipterocarpaceae with the value of 0.8179 followed by Leguminosae (0.4570), Moraceae (0.4220), Myristicaceae (0.3202) and Rubiaceae (0.2760). Similarly at species level, dipterocarp tree play significant role in forming riparian plant communities. The water quality status of Sebaling River, Marong Kiri River and Rasau River are classified as class II which is suitable for recreational but need to be treated for supply of domesticated water. Canonical Correspondence Analysis CCA) indicated that the composition of riparian plant species is closely related to these environmental variables. Based on this study, riparian plant communities have strong correlation with water quality parameters depending on the forest types with major or minor disturbances like logging history and anthropogenic disturbances. However, a better understanding can be produce if the study can be extended for a longer period and the plot size should be expanded for a bigger size which can be covered all types of riparian plants communities along the streams including mosses.